DEGENERATIVE AORTIC STENOSIS: PATHOGENESIS AND NEW PRINCIPLES OF TREATMENT - O. V. Andropova; V. N. Anokhin (Столичная издательская компания, 2016)
Aim. To reveal of markers of inflammation and progression of calcification in patients with degenerative aortic stenosis (DAS). Material and methods. A single-stage study was done in 85 patients with degenerative calcification of aortic valve (42 patients with DAS and 43 patients without DAS). The techniques for assessing the severity of aortic valve calcification included ultrasonic diagnostics and multislice spiral computed tomography. Markers of inflammation and lipid profile were investigated.    Results. Higher blood levels of total holesterol and holesterol of low density lipoprotein were revealed in patients with DAS in comparison with patients without DAS. They also had higher levels of inflammation markers: C-reactive protein and interleukin-6. There were significant correlations between DAS severity, lipid metabolism disturbances and inflammation markers. Conclusion. Atherogenesis and inflammation may have pathogenic influence on progression of aortic valve calcification and DAS development by lipid infiltration and endothelium cells damage.